2020
DOI: 10.7717/peerj.10113
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal expansion of human brucellosis in Shaanxi Province, Northwestern China and model for risk prediction

Abstract: Background Human brucellosis imposes a heavy burden on the health and economy of endemic regions. Since 2011, China has reported at least 35,000 human brucellosis cases annually, with more than 90% of these cases reported in the northern. Given the alarmingly high incidence and variation in the geographical distribution of human brucellosis cases, there is an urgent need to decipher the causes of such variation in geographical distribution. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
3
12
1
Order By: Relevance
“…Human brucellosis had an apparent north-to-south geographic expansion trend. Similarly, previous reports concerning the spatiotemporal expansion of brucellosis in Shaanxi Province showed that human cases slowly extended towards the southern region, with significant seasonal fluctuations 10 . Moreover, the incidence rate has declined in previously epidemic northern Shaanxi regions (Yulin, Yan'an, and Weinan Cities), in contrast to the yearly increases in some emerging Guanzhong and southern Shaanxi epidemic regions, such as Hancheng and Xianyang.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Human brucellosis had an apparent north-to-south geographic expansion trend. Similarly, previous reports concerning the spatiotemporal expansion of brucellosis in Shaanxi Province showed that human cases slowly extended towards the southern region, with significant seasonal fluctuations 10 . Moreover, the incidence rate has declined in previously epidemic northern Shaanxi regions (Yulin, Yan'an, and Weinan Cities), in contrast to the yearly increases in some emerging Guanzhong and southern Shaanxi epidemic regions, such as Hancheng and Xianyang.…”
Section: Discussionsupporting
confidence: 59%
“…The latest study focuses on the spatial and temporal distributions and model for risk prediction of human brucellosis in Shaanxi Province between 2005 and 2018. This study showed that human brucellosis cases were mainly distributed in the Shaanbei upland plateau before 2008 and then slowly extended towards the southern region with significant seasonal fluctuations 10 . Multiple climatic factors (air temperature, sunshine duration, rainfall and relative humidity, etc.)…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Moreover, the high incidence of HB is concentrated in northern China, with an apparent shift in the geographic expansion from northern traditional livestock regions to more urban southern inland areas (16). Our previous study conducted in Shaanxi Province demonstrated similar conclusions regarding the spatiotemporal distribution of HB (17). Owing to rapid and sometimes uncontrolled urbanization, people may face closer encounters with infected animals (18).…”
Section: Introductionmentioning
confidence: 71%
“…Shaanxi Province is located in northern China and is adjacent to many northern regions with a high incidence rate of human brucellosis (Liang et al., 2020). The human brucellosis cases were mainly distributed in the Shaanbei upland plateau before 2008 and then slowly extended towards the southern regions, with significant seasonal fluctuation (Z. Yang, Pang, et al., 2020). Understanding seroprevalence in the human population is an important step for identifying the high‐prevalence regions and formulating targeted measures of control and prevention of human brucellosis (Liu et al., 2020).…”
Section: Introductionmentioning
confidence: 99%